An interlocked DNA cascade system for universal probe-based melting curve analysis. Issue 39 (7th October 2020) - Zhang, Wei; Ming, Zhihao; Chen, Na; Liu, Liquan; Liao, Yuheng; Xiao, Xianjin; Wang, Hongbo
Abstract : This method can complete multiplexed detection by merely changing the bridge sequence, replacing the specific and expensive probe. Abstract : Single-base mutations are the most common type of mutation in human diseases. Melting curve analysis is currently one of the most commonly used methods to detect single base mutations. However, the existing melting curve analysis cannot possess universality and robust detection performance simultaneously. Therefore, herein, we invented an interlocked DNA cascade system based universal melting curve analysis (ICU-MCA). The strategy is based on the probe dissolution curve method by designing a bridge strand to achieve an ideal distinction between mutant-type DNA and wild-type DNA. What is more, this method can complete multiplexed detection only by changing the bridge sequence, replacing the specific and expensive probe in a traditional probe based melting curve analysis. We performed 6-plex detection on 6 single-base point mutations in BRAC1/2 genes on synthetic single stranded DNA and verified the compatibility of ICU-MCA and PCR and detected BRCA1/c.2082C>T and BRCA2/c.7397T>C mutations in peripheral blood DNA of ovarian cancer patients. Overall, ICU-MCA is one of the best methods in the field of melting curve analysis for detecting single-base mutations.